KERJASAMA FINLANDIA-INDONESIA MENGENAI ENERGI TERBARUKAN (BIOMASSA) TAHUN 2011-2014 - Tobing, Astria R.; Waluyo, Tri Joko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research describes the cooperation between Finland-Indonesia on renewable energy (biomass) in 2011-2014. Biomass is a renewable energy sources which refers to biological material that comes from organisms that have not been long dead (compared with fossils fuel). The Government of Indonesia; cooperating with The Government of Finland, plans to develop a new renewable energy (EBT) which was presented in “The Energy and Environment Partnership (EEP) with Indonesia” Program. Cooperation with The Finland Governmentis quite suitable because at this time, 80% percents of Finland energy sources derived from biomass.The research method used is a descriptive of qualitative research method about the facts. This research is an explanatory that describe about problem, indication, policies, and actions. In writing techniques, the author’s collect and collate data through library research from several sources like books, journals, articles, websites, the media and others. The author’s also use the concept of cooperation in view the case in this study.This research shows based on the results of energy research sector,Indonesian countered a serious problem, because the rate of energy demand growth exceeds the domestic energy supply. The crude oil and gasoline; that has been imported; force Indonesian people to looking for another energy sources to overcome energy demand that jumped year by year. Finland Government proposed the biomass power plants cooperation in Jakenan (Central Kalimantan) and Riau.Keyword: Cooperation , Indonesia, Finland, Biomass, in 2011-2014